Employer Branding Towards The Intention To Apply For A Job Through Company Reputation As Mediation Variable - Ria Marginingsih; Elin Setiawan (AMAR (Andalas Management Review), 2021)
This study aims to determine the effect of employer branding on the interest in applying for job with the company reputation as a mediating variable. This study usin type survey of quantitative research design. The research sample is 170 active students in Indonesia, for data analysis using statistical tests and calculations using SmartPLS 3.0 analysis. Based on the results of the questionnaire that has been processed using the SmartPLS tool, it shows that the employer branding variable (X) towards the interest applying for job variable (Z) is a significant influence, then the connection of the employer branding variable (X) towards the company reputation variable (Y) is significant, afterwards the company reputation variable (Y) towards the interest in applying for a job (Z) has a significant influence, subsequently shows the path connection between employer branding variable (X) towards the interest in applying for job variable (Z) through the company reputation (Y) as a mediating variable has significant influence.